THE COMPARATIVE ANALYSIS OF ADJECTIVES IN ENGLISH AND UZBEK LANGUAGES - Abirova Nargiza Xayrullayevna; Axmedov Hasan Uzairovich (TADQIQOTLAR.UZ, 2024)
The utilization of adjectives in two distinct languages is the focus of this article, which also makes an analogy between them based on their morphological levels. Eastern and Western linguists view adjectives very differently, even when arranging them side by side to highlight distinctions and similarities. The past is behind us, but you can take control of the present and create it for yourself right now. We have therefore attempted to illustrate some of the similarities and differences between adjectives in the English and Uzbek languages.